PENYAKIT PERIODONTAL DAN KOMPLIKASI KEHAMILAN - Banun Kusumawardani (Fakultas Kedokteran Gigi Universitas Jember, 2013)
Periodontal disease affects oral health in the mast people. Some researches have found and review the relationship between periodontal disease and systemic disease, such as cardiovascular disease, diabetes, stroke, and pregnancy complication. However, there is detailed explanation about the mechanism that analysis how the relationship between periodontal disease and pregnancy complication. The objective of this study was to review biological mechanism that correlated periodontal disease and pregnancy complication. Periodontal disease was able to cause alteration abnormal systemic immune which underlies pregnancy complication. Periodontal pathogen bacteria were directly colonized in placenta, and they caused local inflammation respond that caused pre-maturity and other pregnancy complications.